The development of oral speech of younger schoolchildren in extracurricular activities (Eurasian Research Bulletin, 2022)
The article provides a system of questions and tasks, the use of various methods of language learning. These opportunities allow students to find ways to solve research and creative tasks. A variety of games and practical activities allow for a better study of phonetics, word formation and grammar. It is indicated that the classes are aimed at repeating, clarifying, expanding the initial ideas about the language. As the result the careful and attentive attitude to the correct oral and written speech is formed which in its turn is an indicator of the general culture of a person